2018
DOI: 10.1210/jc.2018-01171
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin reduces TNF-α-induced human hepatocyte apoptosis, autophagy and pyroptosis: role in obesity-associated NAFLD

Abstract: Ghrelin constitutes a protective factor against hepatocyte cell death. The increased acylated/desacyl ghrelin ratio in patients with obesity and NAFLD might constitute a compensatory mechanism to overcome TNF-α-induced hepatocyte apoptosis, autophagy, and pyroptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 59 publications
6
76
0
Order By: Relevance
“…As a nonspecific PDE‐4 inhibitor, pentoxifylline has an ability to raise levels of cAMP and decrease tumor necrosis factor‐alpha (TNF‐α) gene transcription which could be beneficial in the treatment of many inflammatory diseases . Worth noted, hepatocyte cell death was reported to be induced by TNF‐alpha overexpression in hepatic cells of HFD‐fed rats and obese patients with NAFLD . Hence, suppression of NAFLD‐associated TNF‐α overexpression could have a potential role in ameliorating this disease.…”
Section: Introductionmentioning
confidence: 99%
“…As a nonspecific PDE‐4 inhibitor, pentoxifylline has an ability to raise levels of cAMP and decrease tumor necrosis factor‐alpha (TNF‐α) gene transcription which could be beneficial in the treatment of many inflammatory diseases . Worth noted, hepatocyte cell death was reported to be induced by TNF‐alpha overexpression in hepatic cells of HFD‐fed rats and obese patients with NAFLD . Hence, suppression of NAFLD‐associated TNF‐α overexpression could have a potential role in ameliorating this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro studies have shown that UAG exhibits biological activities on cell proliferation and metabolism through combining their cell membranes [35,36]. In addition to its peripheral actions, which include cell senescence, inhibition of apoptosis, and fat metabolism [37], UAG may function in central feeding regulation via combining with other receptors (e. g., corticotropin releasing factor-2 [38], pre-opioid melanocyte corticosteroid [39]). In GHSR-deficient mice, the functional connection between UAG and the GHSR was revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Total cholesterol, HDL-cholesterol, LDL-cholesterol, and triacylglycerol concentrations (Roche) were calculated as previously described. 13 High sensitivity C-reactive protein (CRP) was measured using the Tinaquant CRP (Latex) ultrasensitive assay (Roche). Insulin was measured by an enzyme-amplified chemiluminescence assay (IMMULITE; Diagnostics Products Corp., Los Angeles, CA, USA).…”
Section: Human Study Cohort and Biological Analysismentioning
confidence: 99%